IMPLEMENTASI MODEL PEMBELAJARAN â€œBERKAT ANANGâ€ DI KALANGAN SISWA PENDIDIKAN DASAR BERBUDAYA JAWA - Rahmawati, Fitri Puji; Muhroji, Muhroji; Utami, Ratnasari Diah (Profesi Pendidikan Dasar, 2014)
The purpose of this research is to find a model of strengthening character education inelementary school environment learners Javanese culture. The specific objective of thesecond year is to formulate a model of an active character education and fun in theelementary school students then tested the cultured Javanese character education modelthat is active and fun in the cultured primary school learners Java. The main methoddeveloped in this research is descriptive - qualitative - reflective. The research method willbe implemented in the second year is the collection of data with focus group discussionsinvolving teachers, principals, school committees , and parents / guardians of students .The collected data were analyzed by using a reflective critique. In that year also applieddata collection methods to test the model. The data were analyzed with a heuristic model.This study has several performance indicators of each year. After the first year the indicatoris reached, followed by a search for examples of learning models applied by the teacherin the implementation of character education. Year two indicators to be achieved is thestrong foundation of character education in the elementary sense after FGD with teachers,principals, school committee, and parents / guardians of students. This indicator willexplain: (1) the weaknesses and strengths of the old model of learning in the teaching ofcharacter education, (2) the expectations of elementary education stakeholders aboutcharacter education , (3) application of learning models “ Thanks Sam “ in SD and thesurrounding region of Surakarta , (4) the power of learning model “ Thanks Sam “ as alearning model that is able to strengthen the character of elementary school students ..